2021
DOI: 10.2139/ssrn.3793565
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Infectious Outbreak Inhibits Pain Empathy Mediated Prosocial Willingness

Abstract: BackgroundThe pandemic of COVID-19 sets off public psychological crises and impacts social functioning. Prepandemic research has shown that as the mental resource wears out under long-term distress, empathy exhaustion will happen. While prosocial activities are positively linked to empathy, quantitative research on the pandemic's effect on empathy and prosocial willingness has been insu ciently examined.Prosocial behaviors are carried out during a life-threatening time to promote communication and encourage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
6
4
0
Order By: Relevance
“…In particular, and similarly to the case of heavy physical trauma (Kandel et al, 2000), severe social exclusions are held to trigger regulatory mechanisms to decrease distress, promote coping strategies, and improving resilience towards subsequent painful stimulations (Antico et al, 2018;Bernstein & Claypool, 2012). Our study converges with, but also extend, previous findings, by showing how pandemic-induced isolation: (1) decreases sensitivity to pain, not only in one's own body, but also in the appraisal of others' face (see also Cao et al, 2020); (2) influences preferentially pain-specific facial information.…”
Section: Social Isolation Affects Pain-specific Facial Informationsupporting
confidence: 87%
See 2 more Smart Citations
“…In particular, and similarly to the case of heavy physical trauma (Kandel et al, 2000), severe social exclusions are held to trigger regulatory mechanisms to decrease distress, promote coping strategies, and improving resilience towards subsequent painful stimulations (Antico et al, 2018;Bernstein & Claypool, 2012). Our study converges with, but also extend, previous findings, by showing how pandemic-induced isolation: (1) decreases sensitivity to pain, not only in one's own body, but also in the appraisal of others' face (see also Cao et al, 2020); (2) influences preferentially pain-specific facial information.…”
Section: Social Isolation Affects Pain-specific Facial Informationsupporting
confidence: 87%
“…We also found that social isolation influenced the way participants reacted to the Cyberball game, specifically in relation to pleasantness scores towards/from the co-players (especially those of inclusive nature). Additionally, and reminiscently of what observed by Cao et al (2020) in the Chinese population, the analysis of empathy scores revealed that subjects from the post-lockdown group were less concerned about others' suffering than those from the pre-lockdown group. These results are consistent with previous findings reporting that being left out by others impacted negatively empathic sensitivity, leading to reduced capacity to understand others' suffering and, in turn, decreased motivation to engage in prosocial acts (e.g., to donate money, offer help and cooperate; Coyne et al, 2011;DeWall & Baumeister, 2006;Twenge et al, 2007).…”
Section: Social Isolation Affects Empathic Scoressupporting
confidence: 52%
See 1 more Smart Citation
“…Second, the study was limited to the early stage of the COVID-19 pandemic. Cao et al (2020) showed that empathy and prosocial tendencies decreased in the post-outbreak period. Thus, a different pattern could be expected in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only few studies investigated the consequences of the social restrictions imposed by the COVID-19 pandemic on the processing of others' affective facial information. For instance, Cao et al, (2020) documented how Chinese individuals exhibited lesser sensitivity to videos of people reacting to electric shocks following the lockdown, an effect that was paralleled by decreased empathic scores from validated questionnaires (Davis, 1980). Instead, Meléndez et al (Meléndez et al, 2020) investigated the impact of lockdown on emotional facial recognition comparing the performance of Spanish individuals before and after the confinement.…”
Section: Introductionmentioning
confidence: 99%